AKTIVITAS MANAJEMEN LABA MELALUI POS BAD DEBT EXPENSE - Febriana Ningsih Hoki; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aims to prove that the management did earnings management through a reduction in bad debt expense on companies that are in the consumer goods sector. The existence of earnings management through bad debt expense activity can be seen from the abnormal bad debt expense. This study uses a sample of EPS as a basis grouping companies doing earnings management and companies that do not profit management (suspect firms). This study uses a control variable, namely firm size and return on assets. This study examined the companies that are in the consumer goods sector listed in Indonesia Stock Exchange with a sample of 52 observations. The results showed that the suspect management firms earning management in the form of a reduction in bad debt expense due to suspect firm has a significant influence on the dependent variable. Research results also showed that the return on assets has no impact on earnings management in the form of a reduction in bad debt expense, while firm size has a significant positive effect on earnings management in the form of a reduction in bad debt expense.